PENDAMPINGAN PEMBELAJARAN DARING DAN LURING DI SMA NEGERI 1 PAGUYAMAN KECAMATAN PAGUYAMAN KABUPATEN BOALEMO - Sukrianto Sukrianto; Fibriyanti S. Lakoro (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
In the implementation of education for students at SMA Negeri 1 Paguyaman during the Covid-19 pandemic and after the Covid-19 pandemic, it turned out to have a major impact on the learning process for students at SMA Negeri 1 Paguyaman. Because most students still have limitations, both from the difficulty of getting a network and sometimes giving direct boredom to students at SMA Negeri 1 Paguyaman. The method of implementing community service carried out by the research team or community service team. Community service is carried out using a site survey method, providing materials related to online and offline learning and mentoring students and conducting evaluations. The purpose of implementing community service is to provide assistance to students at SMA Negeri 1 Paguyaman in the implementation of online and offline giving. The results of community service can provide encouragement to students at SMA Negeri 1 Paguyaman in making good use of online and offline learning. Especially in the face of increasingly developing technology.